Experimental investigation of shell and helical coiled heat exchanger with Al2O3 nano-fluid with wide range of particle concentration - Shabi, Omar Ali; Alhazmy, Majed; Negeed, El-Sayed R.; Elzoghaly, Khaled O. (Frontiers in Mechanical Engineering, 2024)
The purpose of this study is to experimentally enhance the heat exchange rate of the shell and helical coil tube heat exchanger by mixing water with aluminum oxide (Al2O3) nanoparticles, as well as to explore the effect of inlet thermal parameters on the performance of the heat exchanger.A test rig was constructed to investigate the influence of particle concentration, and inlet temperatures on the performance of nano-fluid. Parameters such as Nusselt number, pressure drop, performance evaluation criteria (PEC) are considered to rate the performance of the nano-particle with the heat exchanger. In this study a wider range of particle concentration is considered, which varies from 0.0 -0.75 %. Experiments with and without nanoparticles are carried out under identical working conditions. By analyzing the experimental data, it was found that nanoparticles significantly improve the coefficient of heat transfer inside the helically coiled tube. From sensitivity analysis, it is obseerved that there is a slight decrease in Nusselt number of the nanofluid with increase in inlet temperatures of the nano-fluid and the cooling water. Furthermore, it is concluded that an 8.5 % increase in PEC value is observed with increase in particle concentration from 0.15 % to 0.75 %.